Feeding practices during childhood illness and associated factors among mothers of children under 24 month olds in southwest Ethiopia: A Facility-based cross-sectional study design - Diribsa Tizazu Hailu; Vinod Bagilkar; Ebissa Bayana; Tesfaye Asfaw; Merga Garoma Jatu; Assefa Desalew; Mulualem Keneni; Fentahun Meseret; Tigist Demeke (BMC Pediatrics)
Abstract Background Poor feeding practices during childhood illnesses significantly contribute to morbidity and mortality in low-and middle-income countries. However, information on such practices in Africa, especially Ethiopia is limited. Therefore, this study aimed to assess feeding practices for sick infant and young child and associated factors among mothers or caregivers of children under 24 months of age attending public health facilities in Jimma City, 2023. Methods A facility-based cross-sectional study was conducted from May 20 to June 20, 2023, involving 415 participants selected through a systematic random sampling technique.Data were collected through face-to-face interviews using a pretested, structured questionnaire.Data entry and analysis were performed using Epidata version 4.6 and Statistical Package for Social Science version 25.0, respectively. Multivariable analysis using adjusted odds ratio (AOR) with a 95% confidence interval (CI) was conducted to identify factors associated with feeding practices for sick children. A p-value of < 0.05 indicated Statistical significance. Results The study found that 40.20% (95% CI: 35.50, 44.98) of the participants reported good feeding practices. Factors significantly associated with good feeding practices for sick infants and young children included secondary education [AOR = 2.58, 95% CI: 1.14, 5.80], college or university education [AOR = 4.25, 95% CI: 1.68, 10.71], being a housewife [AOR = 2.09, 95% CI: 1.26, 3.44], having infant and young child feeding counselling [AOR = 1.80, 95% CI: 1.06, 3.06], having good knowledge of sick child feeding [AOR = 3.47, 95% CI: 2.00, 6.08], attending postnatal care visits [AOR = 2.12, 95% CI: 1.30, 3.50], and belonging to food-secure households [AOR = 1.78, 95% CI: 1.04, 3.05]. Conclusions The study revealed inadequate feeding practices for sick infants and young children. Therefore, implementing targeted solutions such as offering training programs and support networks for mothers, enhancing parental awareness, encouraging regular postnatal care visits, promoting feeding for sick infants and young children, strengthening nutritional education, and initiating food security initiatives can effectively improve feeding practices among mothers and caregivers during childhood illnesses.